2021
DOI: 10.3390/app11156898
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Numerical Investigations of the Flow Pattern and Evolution of the Horseshoe Vortex at a Circular Pier during the Development of a Scour Hole

Abstract: In the current study, a three-dimensional CFD model is utilized to investigate the variation of the flow structure and bed shear stress at a single cylindrical pier during scour development. The scour development is presented by seven solidified geometries of the scour hole, collected during previous experimental work at different scour stages. Different turbulence models are evaluated and the (k-ω) model is chosen due to its relative accuracy in capturing the flow oscillation and vortex shedding at the pier d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In this study, the local scour at the bridge pier was estimated using empirical equations. Though numerical simulations and flume experiments are used to understand the scour process, to predict the bed shear stresses due to different pier configurations, and to understand the performance of different countermeasures in reducing the scour potential [13][14][15], the resource (human, technical and financial) and time constraints often do not allow the use of such methods in scour prediction, especially if a large number of bridges are to be studied within a short period. Moreover, the numerical investigation has so far been conducted with a uniform circular pier, square cross-section, and piles of different spacing [14], and no studies are reported on the complex pier.…”
Section: Selection Of Empirical Methodsmentioning
confidence: 99%
“…In this study, the local scour at the bridge pier was estimated using empirical equations. Though numerical simulations and flume experiments are used to understand the scour process, to predict the bed shear stresses due to different pier configurations, and to understand the performance of different countermeasures in reducing the scour potential [13][14][15], the resource (human, technical and financial) and time constraints often do not allow the use of such methods in scour prediction, especially if a large number of bridges are to be studied within a short period. Moreover, the numerical investigation has so far been conducted with a uniform circular pier, square cross-section, and piles of different spacing [14], and no studies are reported on the complex pier.…”
Section: Selection Of Empirical Methodsmentioning
confidence: 99%